Tpreserving cultural heritage through language maintenance: semai oral tradition and knowledge transfer / Sharina Saad...[et al.] - Saad, Sharina; Abdul Aziz, Nurazila; Rahman, Azlan Abdul (Universiti Teknologi MARA, Kedah, 2013)
Languages are perhaps our most powerful instruments for preserving and developing heritage and culture. Cultural heritage is seen as the total ways of living built up by a group of human beings, which is passed down from one generation to the next, given to them by reasons of their birth. However, the loss of a language may also risk the loss of culture at large. In Malaysia the Indigenous communities as well as the Semai, keep their cultural heritage alive by passing their knowledge, arts, rituals and performances from one generation to another, speaking and teaching languages, protecting cultural materials, sacred and significant sites and objects. However, these activities and teachings, if not preserved will soon die out. The lack of Indigenous education would continue to set indigenous youth apart from their own cultures. Therefore the researchers find the significance of educational instruction to take place in Indigenous languages. Efforts have been taken by the researchers to preserve, protect and promote Indigenous culture through cultural education via Indigenous folklores. This is done to raise the community awareness and education on preserving the Semai cultures and language heritage. The documentation of Semai language and folklores is significant because when the Semai language dies out, parts of a culture of the Semai dies.